Why reinvent the wheel? Lessons in schistosomiasis control from the past. - Clive Shiff (Public Library of Science (PLoS), 2017)
Schistosomiasis has been of concern to local health authorities for most of the last century, and in spite of a lack of effective chemotherapy, the disease was dealt with quite effectively in many endemic countries by snail control and environmental management [1]. Much of this work was reported in journals prior to the electronic era but, sadly, seems to have been subsequently ignored. For many years, there followed a global hiatus on schistosomiasis control, and much of the local expertise was lost, but many things have changed more recently, mainly with the advent of generic and affordable praziquantel. With the increased availability of this drug, there has been an increasing interest in readdressing schistosomes as well as other neglected tropical diseases (NTDs). The strategic approach for this had been based almost exclusively on chemotherapy. Recently, however, questions arose about this strategy with evidence that chemotherapy alone was not succeeding [2]. Additional strategies were needed, and the "Towards Elimination of Schistosomiasis" (TES) 2017 Conference in Cameroon stressed an integrated PHASE strategy. This was in line with the WHO-NTD and WHO-AFRO 2014-2020 Regional Strategy on NTDs and directed emphasis on transmission control. Subsequently, this emphasis was discussed in a comprehensive review [3] that stressed the importance of such additions to any elimination programme. In reality, this means focusing on the aquatic snail hosts where and when transmission occurs, defining other risk factors such as water contact and latrine design and identifying improved sanitation and health education as essential components for elimination. For schistosomiasis reduction during the mid-20th century, transmission control was used extensively, but these facts are not well reported. Recent reviews have attempted to cover previous research [4,5], but sadly, they have left major knowledge gaps, particularly from Africa. These omissions also occurred in a recent WHO pamphlet on molluscicides [6]. Sadly, search engines used to retrieve information appear to miss much done by 5 African research institutes active from 1950 to 1990. It seems appropriate to take a look back to a time when fieldwork was a focus of research and transmission control was emphasised.